PELATIHAN PUBLIC RELATION OFFICER BAGI STAF KEHUMASAN SMA NEGERI SUMATERA SELATAN PALEMBANG - Sri Gustiani; Risnawati (Politeknik Negeri Sriwijaya, 2023)
This collaboration community service of lecturers and students was aimed to provide Public Relations (PR) Officer training for the public relation staff at SMAN Sumatera Selatan, Palembang. As an internationally oriented educational institution, this senior high school requires reliable public relations staff. From the initial interview/survey, the problems faced by the school's public relations staff was a lack of knowledge and training in public relations services. The implementation of this community service was carried out for four months starting with an initial survey, counseling, service, mentoring and evaluation. The rationale for administering this public education program is the lecturers and students. The lecturers who involved were certified by the National Professional Certification Agency (Badan Nasional Sertifikasi Profesi/BNSP) and the students have taken PR courses. The results of training and mentoring show that the participants gained (1) knowledge in planning public relations programs to build good relations with the public and media, (2) ability to prepare presentations, events, seminars, conferences, workshops and meetings and document these activities, (3) capable of serving as master of ceremonies, and (4) conducting public relations research in exploring various options to build a good image for the institution. The output was a public relations handbook, final report and an articles published in local/national journals.